2021
DOI: 10.3390/ijerph18041722
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Fitness and Work Ability among Physical Therapists

Abstract: The Work Ability Index (WAI) is a validated and widely used tool in occupational research. However, normative values for physical therapists (PTs) by age and sex are lacking. Although the nature of PTs’ work is physically demanding, it is unknown whether muscular fitness is associated with their WAI. This study sought to provide reference WAI data for Spanish PTs and to evaluate the association between PTs’ muscular fitness and WAI. Data on WAI of 1005 PTs were collected using a questionnaire. A subgroup (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In these studies, muscular strength and endurance of upper body, trunk and lower body muscles were found to associate positively with work ability (Nygård et al 1991 ; Pohjonen, 2001 ; Smolander et al 2010 ), but findings were somewhat conflicting for cardiorespiratory fitness (Nygård et al 1991 ; Pohjonen 2001 ; Sörensen et al 2007 ). During the last 10 years, studies have focused on the associations between muscular strength (upper body, trunk) and work ability among middle-aged employees mostly from manual occupations, and modest associations have been found (Boschman et al 2017 ; Edlund et al 2012 ; Ezzatvar et al 2021 ). However, work life has changed during the last decades in the developed countries, as many physical work tasks have become less physically strenuous due to technological developments, and sedentary office work has become more common (Ng and Popkin 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, muscular strength and endurance of upper body, trunk and lower body muscles were found to associate positively with work ability (Nygård et al 1991 ; Pohjonen, 2001 ; Smolander et al 2010 ), but findings were somewhat conflicting for cardiorespiratory fitness (Nygård et al 1991 ; Pohjonen 2001 ; Sörensen et al 2007 ). During the last 10 years, studies have focused on the associations between muscular strength (upper body, trunk) and work ability among middle-aged employees mostly from manual occupations, and modest associations have been found (Boschman et al 2017 ; Edlund et al 2012 ; Ezzatvar et al 2021 ). However, work life has changed during the last decades in the developed countries, as many physical work tasks have become less physically strenuous due to technological developments, and sedentary office work has become more common (Ng and Popkin 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Work demands and control differ between different healthcare professions and interventions must be tailored to this [ 41 ]. For instance, muscular fitness and age have been related to work ability among physical therapists [ 42 ]. A qualitative study has identified age, skills and training as possible barriers for returning to work among persons with musculoskeletal pain and reduced work ability.…”
Section: Discussionmentioning
confidence: 99%
“…The educational institutions for people with disabilities should prepare them for the acquisition of autonomy and necessary functional independence, which will allow them to develop and, as far as possible, acquire an occupation that commonly requires MS. In this way, it can act as a facilitator of neuromuscular actions when standing [ 25 ], associated with carrying out work activities [ 26 ]. Prospective studies that analyze HGS behavior over time present different trends in the follow-up of children, adolescents [ 27 ] and adults [ 28 ].…”
Section: Introductionmentioning
confidence: 99%